The influence of Platelet-rich fibrin on the inflammatory response, bone metabolism and cell differentiation ability of Temporomandibular joint osteoarthritis - Zhao, Yuhan; Dai, Hongwei (Journal of Medical Biochemistry, 2025)
Objective: This study aims to explore the regulatory effects of platelet-rich fibrin (PRF) on serum inflammatory response, bone metabolic balance and cell differentiation ability in patients with temporomandibular joint osteoarthritis (TMJ-OA) at the molecular levels. Methods: Sixty patients randomly divided into Group A and Group B (30 cases in each group). Group A was treated with meloxicam dispersible combined with hydroxychloroquine sulfate (HCQ); Group B was supplemented with autologous PRF intra-articular injection on the basis of Group A. Fasting venous blood was collected before treatment and 3 months after treatment. Inflammatory and bone metabolism markers such as IL-1β, IL-6, TNF-α, OPN, ALP, and Runx2 were detected by ELISA, and coagulation indicators such as APTT and PT were determined by an automatic coagulation analyzer. Results: After treatment, the inflammatory factors (IL-1β, IL-6, TNF-α) in both groups decreased significantly, but the decrease in group B was more significant (P<0.001). Bone metabolism indicators showed that the improvement in group B was significantly better than that in group A (P<0.05). Among the cell differentiation-related factors, the expression levels of Runx2, TGF-β1 and Sox9 in group B were significantly increased compared with those before treatment (P<0.05), and were higher than those in group A (P<0.05). In terms of coagulation function, the APTT and PT in group B were prolonged (P<0.001), and the levels of FIB and D-D decreased (P<0.001). Conclusion: The use of PRF can optimize the therapeutic effect of TMJ-OA, improve inflammatory responses, promote cell differentiation and reverse the hypercoagulable state of the blood.